One-punch man. 18, Limiter - ONE, 1986- (Shonen Jump manga., 2019)
Life gets pretty boring when you can beat the snot out of any villain with just one punch. Nothing about Saitama passes the eyeball test when it comes to superheroes, from his lifeless expression to his bald head to his unimpressive physique. However, this average-looking guy has a not-so-average problem<U+2014>he just can<U+2019>t seem to find an opponent strong enough to take on! Garo has just left the Monster Association<U+2019>s hideout when he crosses paths with Saitama, who<U+2019>s in quite a pickle, but Saitama still doesn't know Garo is the Hero Hunter. Later, King the Ripper can no longer hold back his murderous urges and confronts Garo himself!